Acculturation and health-related quality of life: results from the German National Cohort migrant feasibility study - Brand, Tilman; Zimmermann, Heiko (International journal of public health, 2017)
Objectives: We assessed the association between acculturation and health-related quality of life (HRQoL) among persons with a Turkish migrant background in Germany.Methods1226 adults of Turkish origin were recruited in four German cities. Acculturation was assessed using the Frankfurt Acculturation Scale resulting in four groups (integration, assimilation, separation and marginalization). Short Form-8 physical and mental components were used to assess the HRQoL. Associations were analysed with linear regression models.ResultsOf the respondents, 20% were classified as integrated, 29% assimilated, 29% separated and 19% as marginalized. Separation was associated with poorer physical and mental health (linear regression coefficient (RC) = −2.3, 95% CI −3.9 to −0.8 and RC = −2.4, 95% CI −4.4 to −0.5, respectively; reference: integration). Marginalization was associated with poorer mental health in descendants of migrants (RC = −6.4, 95% CI −12.0 to −0.8; reference: integration).ConclusionsSeparation and marginalization are associated with a poorer HRQoL. Policies should support the integration of migrants, and health promotion interventions should target separated and marginalized migrants to improve their HRQoL.